1993
DOI: 10.1073/pnas.90.13.5939
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an ethylene-responsive region in the promoter of a fruit ripening gene.

Abstract: Transcription of the E4 gene is controlled by an increase in ethylene concentration during tomato fruit ripening. To investigate the molecular basis for ethylene regulation, we have examined the E4 promoter to identify cis elements and trans-acting factors that are involved in E4 gene expression. In transgenic tomato plants a chimeric gene construct containing a 1.4-kilobase E4 promoter fused to a f-glucuronidase reporter gene Is rapidly induced by ethylene in ripening fruit. Deletion of E4 promoter sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
155
0
4

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(161 citation statements)
references
References 27 publications
(19 reference statements)
2
155
0
4
Order By: Relevance
“…This 8-bp element has been previously identified as an ethylene-responsive enhancer in the tomato E4 and carnation (Dianthus caryophyllus) GST1 genes, both responsive to ethylene. Footprinting analysis has indicated that this sequence corresponds to a specific transcription factor binding site (Montgomery et al, 1993;Itzhaki et al, 1994). The participation of these putative ERE boxes in the regulation of TLC1.1 expression was demonstrated through promoter mutation analyses.…”
Section: The U3 Domain Of Tlc11 5# Ltr Includes Cis-acting Eresmentioning
confidence: 96%
“…This 8-bp element has been previously identified as an ethylene-responsive enhancer in the tomato E4 and carnation (Dianthus caryophyllus) GST1 genes, both responsive to ethylene. Footprinting analysis has indicated that this sequence corresponds to a specific transcription factor binding site (Montgomery et al, 1993;Itzhaki et al, 1994). The participation of these putative ERE boxes in the regulation of TLC1.1 expression was demonstrated through promoter mutation analyses.…”
Section: The U3 Domain Of Tlc11 5# Ltr Includes Cis-acting Eresmentioning
confidence: 96%
“…In their study, GUS gene expression was similar when either a 396 bp or an 1825 bp fragment of the LEACO1 gene promoter was used. While the 1825 bp fragment contained a number of short motifs that have been reported to be important for regulating expression of many genes involved in stress response (Goldsbrough et al 1993) during senescence or for ethylene response (Itzhaki et al 1994;Montgomery et al 1993) the 396 bp fragment promoter sequence did not include any of these short motifs. In our study, the 821 bp fragment of the LEACO1 promoter sequence that we used to drive IPT (and GUS) expression included two copies of the TCA motif (Goldsbrough et al 1993) and one copy of the 8 bp ethylene responsive element (Itzhaki et al 1994;Montgomery et al 1993), plus multiple copies of the TGTCTC sequence that is essential for AuxREs and the Gbox motif associated with some auxin-responsive genes (Menkens et al 1995;Guilfoyle et al 1998 (Li et al 1992;Gan and Amasino 1997;McCabe et al 2001;Schroeder et al 2001;Clark et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Blume and Grierson (1997) report the 10 bp TCA motif (5'-TCATCTTCTT-3') occurs seven times (allowing two substitutions) in the LEACO1 promoter between nucleotides -667 and -1447, and an 8 bp element (5'-AA/TTTCAAA-3') is present in three copies between nucleotides -473 and -1662. The TCA motif is present in the 5' upstream region of over 30 stress-and pathogen-inducible genes (Goldsbrough et al 1993) while the 8 bp element is reportedly necessary for ethylene-response in the carnation GST1 (Itzhaki et al 1994) and the tomato E4 (Montgomery et al 1993) gene promoters.…”
Section: Introductionmentioning
confidence: 99%
“…By screening the 1,736-bp upstream regulatory region of the CsSCR gene with three cis-element recognition programs, we detected a number of potentially interesting sequence motifs: TGCAAAG and AACAAAC, which are necessary for endosperm-specific gene expression (Wu et al 2000); TATCCA and TATCCAC, responsible for the gibberellin response (Lanahan et al 1992;Gubler and Jacobsen 1992); ATTTCAAA, an ethylene-responsive element (Itzhaki et al 1994;Montgomery et al 1993); CCTTTT, which is found in the promoter of the a-amylase gene expressed in embryos and induced by gibberellins (Morita et al 1998;Mena et al 2002); and TGCATG and ACGTG, two ABAresponsive elements (Hattori et al 1992;Hobo et al 1999) (Tab. S2).…”
Section: Csscr Gene Characterizationmentioning
confidence: 99%